DEVELOPMENT OF BULLETIN LEARNING MEDIA ON THE CONCEPT OF FOSSIL FUEL - Zulfadli Zulfadli; Latifah Hanum; Musfira Arisandi (Chimica Didactica Acta, 2020)
This study aims to develop a bulletin on petroleum material and analyze the feasibility and describe the teacher's response to the bulletin learning media on petroleum material. The research method used is research and development (research and development) with the ADDIE model which consists of five steps, namely analysis, design, development, implementation and evaluation. Data collection was carried out online by distributing a google form questionnaire through the WhatsApp Messenger messaging application to 27 chemistry teachers who teach at the Senior High School (SLTA) of South Aceh Regency. The feasibility of the bulletin media was assessed by two media validators with a percentage of 91.66% with very decent criteria. The percentage of teacher responses to the bulletin media that was developed was 97.94% with a very good category. Based on the results of the study, it can be concluded that the bulletin media developed is suitable for use in the petroleum learning process.